POLITENESS STRATEGIES FOUND IN JIMMY FALLON INTERVIEW WITH TRAVIS SCOTT ALBUM UTOPIA - Lavinia Rosemary; Robby Satria (PROJECT (Professional Journal of English Education), 2024)
A gesture of positive politeness is intended to make up for the addressee's positive face, which expresses his persistent desire to have his needs (or the behaviors, assets, or values they create) accepted as acceptable. In order to partially satisfy the addressee's want, redress entails communicating that one's own needs (or some of them) are analogous to those wants in certain aspects.A type of positive attitude based on the polite theory proposed by Brown and Levinson (1987) is analyzed and described using qualitative descriptive methods. After this analysis, the collected data are analyzed using the response theory proposed by Brown and Levinson (1987) to show the listener's response to the positive attitude applied in the interview. From the analysis the researcher found six data that show positive politeness.